Effect of microbial consortia on the Solanum lycopersicum - Fusarium oxysporum f. sp. lycopersici pathosystem - Limon-Corona, Mónica Lorena; Flores-Olivas, Alberto; Hernández-Castillo, Francisco Daniel; Gonz´alez-Merino, Ana María; Gonzalez-Morales, Susana; Virgen-Calleros, Gil; Cerda-García, Pedro Aarón; Hernández-Martínez, Rufina (Ecosistemas y Recursos Agropecuarios, 2022)
The objective was to evaluate the in vitro antagonism of three microbial consortia on three strains of Fusarium oxysporum f.sp. lycopersici (Fol) and their effect on tomato (Solanum lycopersicum) seedlings with wilt symptoms, under greenhouse conditions. The microbial consortia evaluated were Soil Pro (SP), SOS® (SOS) and SSB® (SSB),from Liventia™, composed of bacteria, yeasts and mycorrhizae. The poisoned medium technique was used to determine in vitro antagonism. In the greenhouse, the three consortia were applied to tomato seedlings inoculated with Fol and the following were evaluated: plant height, stemdiameter, chlorophyll content, aerial biomass dry weight, root dry weight and wilt incidence and severity. In the greenhouse test, SP increased the growth of tomato seedlings by 21%, while SP and SOS reduced seedlingdamage by 37%.
Keywords: biological control; incidence and severity; in vitro antagonism; plant growth-promoting rhizobacteria; tomato wilt